Unsteady conjugate heat transfer characteristics in hexagonal cavity equipped with a multi-blade dynamic modulator. (January 2023) - Ikram, Maruf Md.; Saha, Goutam; Saha, Suvash C.
Highlights: An increase of 57.1% heat transfer rate modulator is observed from re  = 100 to re  = 10 3 . The modulator best serves its purpose at the lowest ra and the highest re . The effect of blade number on the thermal performance improvement is trivial. Thermal effectiveness and storage capacity have inverse relationship with each other. Abstract: Purpose: The transient analysis of the thermal response and frictional loss characteristics for flow-modulated conjugate heat transfer phenomena has been investigated in the present study. The flow domain is a partitioned cavity of a hexagonal structure equipped with a multi-blade flow modulator. The clockwise rotating blade is adiabatic and stirrers the internal flow along with the natural convection caused by the bottom heated floor of uniform heat flux. The conjugate behavior is introduced through the solid subdomains consisting of two brick-made partitions and one glass partition of uniform thickness. The material of the partition wall reflects the physical aspects of industrial applications. Approach: The two-dimensional unsteady continuity, momentum, and energy equations are expressed in a non-dimensional form where the buoyant force is modeled through the Boussinesq approximation. The Arbitrary Lagrangian Euler (ALE) finite element is adopted to solve the moving mesh problem by formulating a free triangular discretization scheme. Parametric computational investigations are carried out for air as the working fluid (Pr = 0.71) and 3 different configurations of the rotating modulator while varying the other parameters, i.e., Reynolds number ( Re ) and Rayleigh number (Ra) for a fixed Biot number (Bi = 10 4 ). This dynamic mesh problem encompasses a wide range of parameters, i.e., (100 ≤ Re ≤ 10 3 ), and (10 4 ≤ Ra ≤ 10 6 ) for Bi = 10 4 to evaluate the thermodynamic response of the present thermo-fluid system. Various thermo-fluid system responses are visualized through the spatially average Nusselt number evaluated on the heated surface, system effectiveness, average thermal storage capacity, and frictional power loss of the flow domain. The thermal response is fragmented into individual responses in terms of component signal frequency by the Fast Fourier Transform (FFT) analysis. Findings: According to the current analysis, increasing the number of blades increases the rate of heat transfer by a negligible amount. On the other hand, among three different types of modulators, the three-blade modulator shows the lowest power loss coefficient and the lowest power instability. Thus, a three-blade modulator qualifies as the optimum design to impart external motion to the working fluid to introduce forced convection. Limitations: This research has some scope for improvement. Future studies can be conducted on the improvement of blade designs, thickness, and size of the blades. Practical Implications: The present study can shed light on the modeling of a better storage system where heat transfer and moisture control are integrated for the proper functioning of the storage, such as food storage, cold storage, garment inventory, etc. Originality: This study is original, and no previous research has been conducted considering the hexagonal domain and variation of the number of blades. Conclusion: The present study reveals that a modulator best serves its purpose at low Rayleigh and high Reynolds numbers. Moreover, the three-blade modulator has the lowest power loss coefficient and lowest power instability, making it the most suitable modulator to impart external excitation to the working fluid.